PENGARUH METODE BERMAIN PERAN TERHADAP PERKEMBANGAN NILAI AGAMA DAN MORAL ANAK USIA DINI(Kuasi Eksperimen di Kelompok B RA Al-Muhajir Panyileukan Kota Bandung) - Mira Karmila; Arif Nursihah (CV. ADIBA ASIHA AMIRA, 2025)
This research is motivated by the problems found during the initial observation that the development of religious and moral values of children in Group B RA Al-Muhajir Panyileukan Bandung City has not developed optimally. This can be seen that children rarely say greetings when they arrive at school, children have not been able to behave well when playing with their friends, when praying activities do it with a screaming voice. Therefore, researchers used the role-playing method to determine its effect on the development of children's religious and moral values. The purpose of this research conducted in Group B RA Al Muhajir Panyileukan Bandung City is to find out: 1) The development of children's religious and moral values through the role- playing method in the experimental class; 2) The development of children's religious and moral values through the storytelling method in the control class; and 3) The difference in the development of children's religious and moral values between using the role-playing method and the storytelling method. This research method is a quasi-experiment with a nonequivalent control group design and through pretest, treatment and posstest patterns on two groups to determine the development of religious and moral values in children. Class B1 as many as 15 children (control class) and class B2 as many as 15 children (experimental class). The results of data analysis show that the development of religious and moral values of early childhood before being given treatment using the role-playing method obtained an average value of 54 and after being given treatment using the role-playing method obtained an average value of 88. While the development of religious and moral values of children before being given treatment using the storytelling method obtained an average value of 47 and after being given treatment obtained an average value of 74. Based on the results of hypothesis testing obtained t_hitung = 2.903> t_ (table) = 1.701 then H_0 (null hypothesis) is rejected and H_1 (alternative hypothesis) is accepted. This means that there is a difference in the development of religious and moral values in children between learning using the role-playing method and the storytelling method in Group B RA Al Muhajir Panyileukan Bandung City.